KERANGKA DASAR DAN LANDASAN PENGEMBANGAN KURIKULUM 2013 - Suarga, Suarga (Universitas Islam Negeri Alauddin Makassar, 2017)
The history of education travel in Indonesia, the curriculum has become a negative stigma in society because of frequent change but the quality is still doubtful. The curriculum is a means to achieve the desired educational program. As a means, the curriculum will be meaningless if it is not supported by the necessary facilities and infrastructure such as adequate teaching and learning resources, the ability of the teaching staff, appropriate methodology, and clarity of direction and objectives to be achieved. Fundamentals of the 2013 curriculum, according to Mulyoto is a matter of learning approach. During this time, the approach used is the material. So the material given to the students as much as possible so that they master the material to the fullest. Even for the sake of mastery of the material, drilling has been given since the beginning, long before students face the national exam. In such learning, learning objectives of learning objectives are achieved more to the kognitif aspect by negating the psychometric and affective aspects.